2009
DOI: 10.3762/bjoc.5.57
|View full text |Cite
|
Sign up to set email alerts
|

Saddle-shaped tetraphenylenes with peripheral gallic esters displaying columnar mesophases

Abstract: SummaryTetraphenylenes 2 with eight peripheral gallic esters were prepared in two steps from octamethoxytetraphenylene 1 in 19–72% yield. Investigation of the mesomorphic properties of 2 by DSC, POM and X-ray diffraction revealed that derivatives 2a–d with short alkoxy chain lengths (C5–C8) did not show any mesomorphic properties, whereas compounds 2e–i with C9–C13 chains displayed rectangular columnar mesophases and compounds 2j–l with C14–C16 chains displayed hexagonal columnar mesophases. Furthermore an ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…299 Based on prior work dealing with octaalkyloxy-and octaacyloxysubstituted tetraphenylenes 300,301 the groups of Laschat and Giesselmann discovered an odd−even effect for discotics such as 114−116 for the first time (Scheme 51, Figure 31). 302,303 More recently, Hau et al introduced alkoxy and oligoethylene glycol substituents in the 1,8,9,16-position of the core resulting in chiral tetraphenylene derivatives with SmA phases. 304 Thiery et al reported hexacatenar spiro-fluorenes 117 with terminal gallic acid amides, which showed Col and Cub phases and were strongly luminescent (Scheme 52).…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…299 Based on prior work dealing with octaalkyloxy-and octaacyloxysubstituted tetraphenylenes 300,301 the groups of Laschat and Giesselmann discovered an odd−even effect for discotics such as 114−116 for the first time (Scheme 51, Figure 31). 302,303 More recently, Hau et al introduced alkoxy and oligoethylene glycol substituents in the 1,8,9,16-position of the core resulting in chiral tetraphenylene derivatives with SmA phases. 304 Thiery et al reported hexacatenar spiro-fluorenes 117 with terminal gallic acid amides, which showed Col and Cub phases and were strongly luminescent (Scheme 52).…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…The structure of 8 was confirmed by 1 H NMR and 13 C NMR spectroscopy, and its absolute configuration was fully established by an X-ray crystallographic analysis (Figure 3).…”
Section: ■ Introductionmentioning
confidence: 84%
“…In this study, the chiral pieces were synthesized following the chiron approach starting with enatiomerically pure butane-2,3-diols. Owing to their unique structures and intriguing properties, optically pure and racemic substituted tetraphenylenes could be applied in the field of asymmetric catalytic hydrogenation, organic catalysis, liquid crystals, and molecular devices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Tetraphenylene (3) displays a saddle-shaped structure with two opposite pairs of benzenoid rings alternating up and down the plane of a central cyclooctatetraene hub. Tetraphenylene can be considered as a valuable building block for [8] circulenes following intramolecular stitching methodologies, but this molecule and derivatives have also shown outstanding capabilities as liquid crystals, [24][25][26] molecular devices, 27 and chiral ligands in catalysis. [28][29][30][31][32][33] In addition, the establishment of heteroatom bridges in tetraphenylene rings planarizes the scaffold, becoming potential candidates for electronic materials with new semiconductor properties.…”
Section: In-out Cyclization Strategy (Intramolecular Stitching)mentioning
confidence: 99%